Modern Principles of the Course of Coronavirus Infection in Patients with Arterial Hypertension (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Taking into account the number of victims of a new coronavirus infection caused by the SARS-CoV-2 virus (COVID-19), on March 11, 2020, the World Health Organization declared a pandemic. Since December 2019, when the first case of SARS was detected in China, the first data have appeared on the characteristics of the course of infection in patients with various diseases. In particular, there have been reports of a greater susceptibility to infection in persons with cardiovascular diseases and, in particular, with arterial hypertension, and a significantly higher risk of adverse outcomes in this group of patients. [Konradi A.O., 2020] We provide an analysis of the available to date, publications relating to people with arterial hypertension who have had a coronavirus infection. Reviews, clinical guidelines and original articles published from 2010 to 2020 were analyzed.